Proprietorship, Funding Practices and Quality Education Delivery of Public Secondary Schools in Delta State, Nigeria - MOSES-PROMISE, Omonefe Jemilatu; OKONTA, Vinella (Ilorin Journal of Education, 2024)
This study investigated proprietorship, funding practices and quality education delivery of public secondary schools in Delta State, Nigeria. The design for the study was the correlational research design. Two research questions and hypotheses were formulated to guide this study. 489 principals from public secondary schools in Delta state constituted the population and sample size of 100 principals representing 20% drawn from the total number of principals in public secondary schools in Delta state using the Taro Yemen. An instrument called Proprietorship, Funding Practices and Quality Education Delivery Questionnaire (PFPQEDQ) was used for data collection and its reliability coefficient was computed at 0.82 using cronbach alpha method. Simple regression was used to analyze the research questions and t-test associated with simple regression was used to test the null hypotheses. Findings of the study revealed that deregulation has contributed averagely to quality education delivery and that public private partnership has also contributed highly to quality education delivery in public secondary schools in Delta state. It was recommended among others that the state government should come up with a plan on the extent to which secondary education will be deregulated, the state government should encourage public private partnership to a great extent as it will reduce the problem of underfunding of secondary schools.